An aqueous, organic dye derivatized SnO2/TiO2 core/shell photoanode. Issue 8 (15th October 2015) - Wee, Kyung-Ryang; Sherman, Benjamin D.; Brennaman, M. Kyle; Sheridan, Matthew V.; Nayak, Animesh; Alibabaei, Leila; Meyer, Thomas J.
Abstract : Visible light driven water splitting in a dye-sensitized photoelectrochemical cell (DSPEC) based on a phosphonic acid-derivatized donor–π–acceptor (D–π–A) organic dye (P–A–π–D) is described with the dye anchored to an FTO|SnO2 /TiO2 core/shell photoanode in a pH 7 phosphate buffer solution. Abstract : Visible light driven water splitting in a dye-sensitized photoelectrochemical cell (DSPEC) based on a phosphonic acid-derivatized donor–π–acceptor (D–π–A) organic dye (P–A–π–D) is described with the dye anchored to an FTO|SnO2 /TiO2 core/shell photoanode in a pH 7 phosphate buffer solution. Transient absorption measurements on FTO|TiO2 |–[P–A–π–D] compared to core/shell, FTO|SnO2 /TiO2 (3 nm)|–[P–A–π–D], reveal that excitation of the dye is rapid and efficient with a decrease in back electron rate by a factor of ∼10 on the core/shell. Upon visible, 1 sun excitation (100 mW cm −2 ) of FTO|SnO2 /TiO2 (3 nm)|–[P–A–π–D] in a phosphate buffer at pH 7 with 20 mM added hydroquinone (H2 Q), photocurrents of ∼2.5 mA cm −2 are observed which are sustained over >15 min photolysis periods with a current enhancement of ∼30-fold compared to FTO|TiO2 |–[P–A–π–D] due to the core/shell effect. On surfaces co-loaded with both –[P–A–π–D] and the known water oxidation catalyst, Ru(bda)(pyP)2 (pyP = pyridin-4-methyl phosphonic acid), maximum photocurrent levels of 1.4 mA cm −2 were observed which decreased over an 10 min interval to 0.1 mA cm −2 . O2 was measured by use of a two-electrode, collector–generator sandwich cell and was produced in low faradaic efficiencies with the majority of the oxidative photocurrent due to oxidative decomposition of the dye.